Analisis Efektivitas Produksi dengan Metode Total Productive Maintenance (TPM) Pada Mesin Ring Spinning (Studi Kasus : PT. XYZ) - Zakiyyan Zain Alkaf; Nadia Nanzah; Bhre Wangsa Lenggana (Badan Kerja Sama Teknik Mesin Indonesia, 2025)
PT. XYZ is a textile manufacturer specializing in polyester/cotton-blended fabrics and yarns. A critical machine in its production process, the ring spinning machine, frequently experiences maintenance issues and breakdowns, resulting in decreased productivity. Production effectiveness was analyzed using the Total Productive Maintenance (TPM) approach, with Overall Equipment Effectiveness (OEE) and the Six Big Losses as key indicators. This study aims to calculate the OEE, identify the most significant losses affecting machine performance, and determine the main factors contributing to low productivity. Results show that the average OEE from June 2024 to January 2025 was 85%, with Availability at 93%, Performance at 92%, and Quality at 99%. Although these values are within a good range, improvements are needed to reach optimal efficiency. The dominant losses were Reduce Speed Losses and Idling & Minor Stoppages (each 7%), followed by Set Up and Adjustment Losses (5%). These were mainly caused by slow production, minor disruptions, and inefficient setup times. Strategic recommendations were proposed to enhance operational efficiency and reduce downtime.